Understanding the Triple Helix Model and Capitalization of Knowledge - Kunwar, Ramesh Raj; Ulak, Nimesh (Journal of APF Command and Staff College, 2023)
This paper is a preliminary study of the Triple Helix (TH) Model that focuses on understanding the model from different perspectives following secondary research. The methodology used in this study is exploratory and descriptive in nature. Narrative review of previous literatures has been followed to understand the Triple Helix Model. Henry Etzkowitz and Loet Leydesdorff propounded a theory known as Triple Helix in connection with industry, university and government which has become a research hub. The Triple Helix is a spiral model of innovation that captures multiple reciprocal relationships at different points in the process of knowledge capitalization. Therefore, this is going to be popular not only in developed countries but also gradually becoming popular in developing countries. The question comes what is Triple Helix Model? What does the model reflects in the academia? The objective of this study is to understand Triple Helix Model on one side and the evolution of this model including its features on the other. This study examines how the Triple Helix Model has been popularized in the field of academia, industry, and government by focusing on knowledge, innovation, and entrepreneurship through education. This paper includes introduction, methodology, evolution of the Triple Helix Model, routes of the Triple Helix, knowledge production, knowledge and technology transfer, knowledge industries, capitalization of knowledge and innovation, the network society, collaboration, Triple Helix and academia, teaching, learning, and future universities. The Triple Helix Model is a neo-evolutionary model of possible synergies between functions such as wealth creation, knowledge production and government regulations, which are the three helixes.